2017
DOI: 10.1080/02668734.2017.1405361
|View full text |Cite
|
Sign up to set email alerts
|

Balint groups in undergraduate medical education: a systematic review

Abstract: This is a repository copy of Balint groups in undergraduate medical education: a systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Traditional Balint-groups are based on voluntary participation, and most student Balint-groups have taken that approach. 38 In our scheme, attendance was initially optional but some students chose to skip the second session, especially in the run-up to examinations. Olds and Malone 36 reported that for two out of their six student sessions, just one of the nine expected students attended, because of ‘medical appointments’ and ‘other teaching commitments’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Balint-groups are based on voluntary participation, and most student Balint-groups have taken that approach. 38 In our scheme, attendance was initially optional but some students chose to skip the second session, especially in the run-up to examinations. Olds and Malone 36 reported that for two out of their six student sessions, just one of the nine expected students attended, because of ‘medical appointments’ and ‘other teaching commitments’.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations have used questionnaires, 35 participant observation, 36 leaders’ observations and students’ reflective essays, 31 formal qualitative analysis 28 and randomised controlled trials. 37 A recent systematic review of Balint-groups in undergraduate medical education 38 found just eight studies (four quantitative, one qualitative and three multi-method) which met the authors’ inclusion criteria of ‘relating to undergraduate medical students’ and ‘relating to interventions which had been labelled as Balint-groups’. It concluded that Balint-groups might help medical students to become more patient-centred, increase students’ empathic abilities and support personal and professional growth.…”
Section: Introductionmentioning
confidence: 99%
“…2 Bristol and Kings College London are unique in trying to ensure that all their first-year clinical medical students participate in a student Balint group. However, when the groups are optional rather than a compulsory part of medical school curricula, they are more valued by students (Monk, Hind & Crimlisk, 2018). The Pan London Medical Student Balint Society has recently been established and the Royal College of Psychiatrists now holds a biannual Medical Student Balint Group and Student Psychotherapy Symposium.…”
Section: Medical Student Balint Groupsmentioning
confidence: 99%
“…If not addressed, academic stress may significantly increase exhaustion, alienation, decrease motivation and alter the perception of learning, these potentially evolving into a welldefinite burnout syndrome at the end of studies or at the beginning of the professional career [15][16][17]. Counseling [18], classic psychotherapy (e.g., cognitive-behavioral therapy, assertive training, or mindfulness) [19][20][21], as well as self-help assemblies (such as Balint groups) [22][23][24] have been used as viable tools to address academic stress; however, their implementation is not systematic. This is partly explained by the particular organizational context of medical universities [25,26], but also by the incomplete clarification of the rela-tionships between the variables contributing to the students' perception of academic stress and their investment in learning.…”
Section: Introductionmentioning
confidence: 99%